Complete vaginal stenosis and hematocolpus in two bitches with a history of GnRH treatment to postpone puberty - MARINO, G.; QUARTUCCIO, M.; SFACTERIA, A.; CRISTARELLA, S.; ZANGHÌ, A. (Journal of the Hellenic Veterinary Medical Society, 2020)
Two mixed-breed bitches (18 and 19 months), that had been treated, one year before, with deslorelin acetate implant to postpone puberty, were hospitalized and monitored during their first heat. The heat was presumed by the owners, that observed vulvar swelling in both cases but no vulvar bloody discharge. The following diagnostic procedures were employed: physical genital tract examination, vaginoscopy, vaginal cytology, endocrine assay, ultrasound and X-ray using vaginal infusion of iodum and pneumobladder as positive and negative contrasts. In bitch 1, vaginal cytology and progesterone levels confirmed the presence of an ovulatory “dry” oestrus, without cytological presence of red blood cells, progressing to dioestrus. Ultrasound showed preovulatory follicles and, in the following days, transition to corpora lutea. The caudal abdomen presented a large ovoid cystic structure filled with echoic fluid, next to the bladder. Radiographic scans demonstrated a normal bladder profile, while the contrast medium failed to enter into the cranial vagina. On the basis of these findings, the bitch 1 was submitted to laparotomy 10 days after the end of oestrus. A vaginal dilatation (10x5 cm), from which brown fluid was aspirated, was found and resected together with uterus and ovaries. Bitch 2 had the same diagnostic route and findings, but she was laparotomized 3 months after the heat. During this period no spontaneous regression of the lesion was observed. At laparotomy, the vaginal dilatation (8x4 cm) was only aspirated and the bitch regularly neutered. In both cases, cytology of the fluid taken from the vaginal sac revealed superficial epithelial cells and abundant degenerate red blood cells. Histology (bitch 1) confirmed the vaginal origin of the dilatation and revealed an additional Gärtner duct cyst. The abnormality (hematocolpus) probably originated by an inadequate drainage of proestrous bloody discharge because of a severe vaginal stenosis. A congenital origin of the lesion was unlikely; it was strongly suspected that the treatment of the prepubertal bitches interfered, by an irreversible way, with the normal development of the vagina.